An Assessment Of Risk Identification In Large Construction Projects In Iran - Tadayon, Mehdi; Jaafar, Mastura; Nasri, Ehsan (Penerbit Universiti Sains Malaysia, 2012)
One of the most important issue that a project manager must address in construction project management is risk management. Risk management includes identifying risks, assessing risks either quantitatively or qualitatively, choosing the appropriate method for handling risks, and then monitoring and documenting risks. By identifying risks in an early stage of planning and assessing their relative importance, project managers can identify methods used to reduce risks and allocate the best people to mitigate them. Thus, this research focuses on risk identification, as opposed to other processes of risk management. In Iran, "brain-storming sessions" is the most popular method used frequently to identify the risks in projects as deduced from a questionnaire survey from participants in large construction projects. Time and cost management need to be fully integrated with the identification process. Time constraints and project managers with sufficient experience are critical when identifying the level of risk for large and/or complex projects. The most considerable types of risk in construction projects are financial risks, construction risks, and demand or product risks.